2018
DOI: 10.1021/jacs.8b03247
|View full text |Cite
|
Sign up to set email alerts
|

Transient Kinetics and Quantum Yield Studies of Nanocrystalline α-Phenyl-Substituted Ketones: Sorting Out Reactions from Singlet and Triplet Excited States

Abstract: Recent work has shown that diarylmethyl radicals generated by pulsed laser excitation in nanocrystalline (NC) suspensions of tetraarylacetones constitute a valuable probe for the detailed mechanistic analysis of the solid-state photodecarbonylation reaction. Using a combination of reaction quantum yields and laser flash photolysis in nanocrystalline suspensions of ketones with different substituents on one of the α-carbons, we are able to suggest with confidence that a significant fraction of the initial α-cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…), stable suspensions of crystalline particles with an average size in the submicrometer regime can be prepared. We term such mixtures nanocrystalline suspensions, which have been shown to be amenable to spectroscopic analysis using standard solution-phase methods. , For each derivative, nanocrystalline suspensions were prepared using a 0.04 mM CTAB surfactant solution and stock solutions in acetonitrile. For ketone 4 , 0.2 mL of a 2.5 mg/mL acetonitrile solution was added dropwise to ∼20 mL of a vortexing surfactant solution.…”
Section: Resultsmentioning
confidence: 99%
“…), stable suspensions of crystalline particles with an average size in the submicrometer regime can be prepared. We term such mixtures nanocrystalline suspensions, which have been shown to be amenable to spectroscopic analysis using standard solution-phase methods. , For each derivative, nanocrystalline suspensions were prepared using a 0.04 mM CTAB surfactant solution and stock solutions in acetonitrile. For ketone 4 , 0.2 mL of a 2.5 mg/mL acetonitrile solution was added dropwise to ∼20 mL of a vortexing surfactant solution.…”
Section: Resultsmentioning
confidence: 99%
“…When R = CHAr 2 , there is a rapid spin-conserving loss of CO to form the relatively long lived triplet alkyl−alkyl radical pair 3 RP-2 (step 4), which goes on to the product 2 (step 7) through the singlet radical pair 1 RP-2 via a ratelimiting intersystem crossing step (step 6) shown to occur with time constants between 40 and 90 μs depending on Ar. 13,14 These rather long lifetimes are a strong indication that short inter-radical distances enforced by molecular crystals and the ensuing large singlet−triplet energy gaps (ΔE ST ) create an entangled spin system with limited intersystem crossing mechanisms. 15−18 As indicated in Figure 1, large ΔE ST values render an intersystem crossing mechanism based on hyperfine electron−nuclear interactions ineffective.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It was noted in a previous report that it is necessary to add a stabilizer such as cetyltrimethylammonium bromide (CTAB) to prevent the nanocrystal from aggregating spontaneously. 19,25,27,29 However, for the nanocrystals of OB and DOB, the stabilizer is not necessary, because the nanocrystalline suspensions of OB and DOB can remain stable for a relatively long time, which can be proven by the temporal dependence of UV−vis absorption spectra (Figure S3). Fs-TA is a powerful technique to detect the excited states and its dynamics processes of photosensitizers.…”
mentioning
confidence: 99%
“…Oxybenzone (OB) and dioxybenzone (DOB) are two commercial ultraviolet (UV) filters that are inevitable ingredients in sunscreens. They both have broad absorption bands, covering UVA and UVB regions with high molar absorption coefficients. , Furthermore, they display an excellent photochemical stability; in other words, they are capable of remaining chemically invariable for a long period. As for their molecular structure, they both contain hydroxyl and carbonyl, which can act as the role of donor and acceptor of hydrogen, respectively, so it can undergo a hydrogen-transfer process in the route of dissipating the energy from UV irradiation. Recent studies have demonstrated a rational energy dissipation mechanism of OB in cyclohexane solvent, indicating that it will mainly consume the energy absorbed from UV irradiation via a circulation of excited-state hydrogen transfer (ESHT), internal conversion (IC), and ground-state hydrogen transfer (GSHT) in the solution phase. Although great progress has been made in the research of sunscreens in the solution phase, there are few reports on the excited states and transient states and its dynamics because of tremendous complicated impacts on the photophysics and photochemistry of organic solid crystals. , However, a nanocrystal whose size is smaller than the irradiating light will maintain the structure of the bulk crystal and it can be suspended in a water solution, resulting in the supramolecular property. As a result, it will lead to a great enhancement in the organic photochemical reaction similar to the reaction in the bulk crystal, exhibiting a very promising potential in photosynthesis as well as material development . The lifetimes of the transients for nanocrystals of small organic molecules can be diverse from that in the solution phase in varying degrees, implying that this characteristic can be used with advantage in numerous areas, such as photocatalysis, organic light-emitting diodes (OLEDs), chemical sensors, biological markers, new fluorescent materials, nonlinear optics, high-density information storage, and so on. , …”
mentioning
confidence: 99%
See 1 more Smart Citation